Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00216-016-9743-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered plasma levels of decanoic acid in colorectal cancer as a new diagnostic biomarker

Abstract: Colorectal cancer (CRC) is one of the most common tumors in developed countries. The five-year survival rate decreases depending on how advanced the CRC is when first diagnosed. Screening has been proven to greatly reduce mortality from colorectal cancer, but an ideal screening tool is far from being established. Here, we aimed to discover and validate early CRC biomarkers by means of an untargeted/targeted metabolomic approach. A preliminary untargeted analysis of plasma lipids performed on a small patient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
2
20
1
2
Order By: Relevance
“…Hata et al (2017) and Ritchie et al (2013) both found gastrointestinal tract acid 446 (GTA-446) to be a promising new biomarker with sensitivity of 83.3% and specificity of 84.8%, 85.7%, and 52.1%, respectively [ 25 , 30 ]. Decanoic acid was also found to be a promising biomarker candidate according to two independent studies with good characteristics (sensitivity 87.87%, specificity 80.0%, 71.0%, and 75.0%, respectively) [ 23 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hata et al (2017) and Ritchie et al (2013) both found gastrointestinal tract acid 446 (GTA-446) to be a promising new biomarker with sensitivity of 83.3% and specificity of 84.8%, 85.7%, and 52.1%, respectively [ 25 , 30 ]. Decanoic acid was also found to be a promising biomarker candidate according to two independent studies with good characteristics (sensitivity 87.87%, specificity 80.0%, 71.0%, and 75.0%, respectively) [ 23 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 summarizes results for metabolites that were assessed three times or more often in combination as potential markers in blood samples. Some studies focused primarily on amino acids [ 27 , 33 , 45 ] or on fatty acids and other lipid derivatives [ 25 , 26 , 29 , 30 , 36 , 41 , 43 , 46 ]. Some metabolites, e.g., arginine, histidine, or tyrosine, were consistently found to be downregulated in blood samples from CRC patients compared to those from healthy controls, but results from other metabolites are not as clear and further research is needed.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of MCFAs, together with their corresponding acyl-carnitines, is the typical feature of medium-chain acyl-coenzyme A dehydrogenase deficiency, the most frequent fatty acid oxidation disorder, and one of the most recognizable inborn errors of metabolism (Rinaldo and Matern, 2002). Nevertheless, recent studies have also associated this metabolic signature with other heterogeneous diseases, such as Alzheimer's disease (González-Domínguez et al, 2014), schizophrenia (Liu et al, 2014) and different types of cancer (Hori et al, 2011, Crotti et al, 2016), all of them characterized by impaired mitochondrial function. Furthermore, it has been demonstrated that these fatty acids can provoke significant failures in various pathways related to energy metabolism, including the oxidative phosphorylation and the creatine kinase system, and may elicit lipid and protein oxidative damage (Schuck et al, 2009).…”
mentioning
confidence: 99%
“…Если для α-линоленовой (октадекатриеновой) Таблица 3. Содержание видов жирных кислот в мембранах эритроцитов и сыворотке крови у пациентов с колоректальным раком и в группе сравнения (M ± SD), % 8,11,14,17) достоверное (p = 0,007) повышение отмечено только в сыворотке крови, хотя и в мембранах эритроцитов наблюдалась та же тенденция. Для докозатетраеновой 7,10,13,16-22:4 кислоты выявлена инверсная ситуация -уровень ее был достоверно выше в мембранах эритроцитов пациентов с КРР (p <0,0001), а в сыворотке отмечена лишь тенденция к повышению (p = 0,097).…”
Section: экспериментальные статьиunclassified
“…Изменения состава ЖК в эритроцитах происходят в более отдаленные сроки, чем в сыворотке крови [6]. Несмотря на то, что в литературе имеются сведения о связи заболеваемости КРР с составом, а также с уровнем ЖК в сыворотке и мембранах эритроцитов, неясно, возможно ли использование отдельных видов ЖК как биомаркеров в диагностике ранних стадий КРР и оценке прогрессирования заболевания: определения как наличия метастазов, так и их преимущественной локализации [7][8][9][10][11]. Другой важный аспект изучения состава и роли отдельных ЖК может быть связан с их перспективным использованием в таргетной терапии КРР [1,[7][8][9].…”
Section: Introductionunclassified